Studies of hemolytical and antimicrobical action of Amanita virosa Secr. and Mycena pura /Fr./ Kumm. poisonous mushrooms lectins - Antonyuk, V.O.; Nemchenko, O.O.; Tymchuk, I.V.; Danileuchenko, V.V.; Stoika, R.S. (Вiopolymers and Cell, 2010)
Aim. To study hemolytical and antimicrobical action of two new lectins, obtained from fruit bodies of poisonous basidial mushrooms of A. virosa Secr. and M. pura /Fr./ Kumm. Methods. Research on hemolytical action of lectins was conducted on the erythrocytes of human and animals. The experiments on osmotic protection of erythrocytes were performed in the presence of polyethylenglycols of different molecular mass (in a range from 400 to 4000 Da). Antimicrobical activity of lectins was studied by determination of area delay of growth of culture of different types of microorganisms on the Petri dish in an agaric media. Results. Both lectins hemolyse the erythrocytes of rabbit, human, rat and dog and do not hemolyse the erythrocytes of cow and ship in concentration of 1 mg/ml. The rabbit erythrocytes are most sensitive to hemolytical action of lectins, while hemolytic ability of A. virosa lectin is higher. Hemolysis was not observed in the presence of PEG of molecular mass over 1,350 Da. Action of lectins on 10 types of microorganisms was investigated. Lectins inhibited mainly growth of grammpositive microorganisms and protey. For most tested microorganisms antimicrobial action of Mycena lectin is stronger comparing with A. virosa lectin. Conclusions. Two new hemolytical lectins are found in the fruit bodies of mushrooms-basidiomycetes. The lectin formed ion-permeable pores in membrane of erythrocytes with the hydrodynamic diameter smaller than 2.3 nm and larger than 1.6 nm. These lectins displays also antimicrobial activity and by the sum of these features are similar to the cytolytic lectins of lower invertebrates. Мета. Дослідити гемолітичну та антимікробну дії двох нових лектинів, одержаних з плодових тіл отруйних грибів-базидіоміцетів A. virosa Secr. та M. pura /Fr./ Kumm. Методи. Гемолітичну дію лектинів вивчали на еритроцитах людини і тварин. Експерименти з осмотичного захисту еритроцитів виконано за присутності поліетиленгліколю різної молекулярної маси (в діапазоні від 400 до 4000 Да). Антимікробну активність лектинів аналізували, визначаючи зону затримки росту культури різних видів мікроорганізмів на чашках Петрі в агаризованому середовищі. Результати. Обидва лектини гемолізують еритроцити кроля, людини, щура та собаки і не гемолізують еритроцити корови й барана у концентрації 1 мг/мл. Найчутливішими до гемолітичної дії лектинів виявилися еритроцити кроля, гемолізуюча здатність лектину A. virosa є вищою. Гемолізу не спостерігалося за присутності поліетиленгліколю з молекулярною масою понад 1350 Да. Досліджено дію лектинів на 10 видах мікроорганізмів. Лектини пригнічують ріст переважно грампозитивних мікроорганізмів і протею. Для більшості випробуваних мікроорганізмів антимікробна дія лектину M. pura є сильнішою, ніж лектину A. virosa Secr. Висновки. Знайдено два нових гемолітичних лектини в плодових тілах грибів-базидіоміцетів. Вони формують у мембранах еритроцитів іоно-проникні пори, гідродинамічний діаметр яких є меншим за 2,3 нм, але більшим за 1,6 нм. Зазначені лектини виявляють також антимікробну активність і за сукупністю цих ознак нагадують цитолітичні лектини нижчих безхребетних. Цель. Исследовать гемолитическое и антимикробное действие двух новых лектинов, выделенных из плодовых тел ядовитых грибов-базидиомицетов A. virosa Secr. и M. pura /Fr./ Kumm. Методы.Гемолитическое действие лектинов исследовали на эритроцитах человека и животных. Эксперименты по осмотической защите эритроцитов выполнены в присутствии полиэтиленгликолей различной молекулярной массы (в диапазоне 400–4000 Да). Антимикробную активность лектинов анализировали, определяя зону задержки роста культуры разных видов микроорганизмов на чашках Петри в агаризованной среде. Результаты. Оба лектина гемолизируют эритроциты кролика, человека, крысы и собаки и не гемолизируют эритроциты коровы и барана в концентрации 1 мг/мл. Эритроциты кролика оказались самыми чувствительными к гемолитическому действию лектинов, при этом гемолизирующая способность лектина A. virosa выше. В присутствии полиэтиленгликоля с молекулярной массой выше 1350 Да гемолиз не наблюдался. Изучено действие лектинов на 10 видов микроорганизмов. Лектины преимущественно подавляют рост граммположительных микроорганизмов и протея. Для большинства исследованных микроорганизмов антимикробная активность лектина мицены выше, чем лектина A. virosa. Выводы. Найдены два новых гемолитических лектина в плодовых телах грибов-базидиомицетов. Они формируют ионо-проникающие поры, гидродинамический диаметр которых меньше 2,3 нм, но больше 1,6 нм. Указанные лектины обнаруживают также антимикробную активность и по совокупности этих признаков напоминают цитолитические лектины низших беспозвоночных.